Assessment of methane enrichment efficacy of pre-disintegrated water hyacinth biomass using sonic wave assisted biosurfactant. (15th May 2022) - Sethupathy, A.; Sobana Piriya, P.; Ranjith Kumar, R.; Shanthi, M.; Rangabhashiyam, S.; Arun, C.; Vasanth Ragavan, K.
Highlights: Sonic wave method was attained minimal biomass lysis rate (15.7 %). Sonic wave coupled Iturin A with alkaline pH method got higher biomass lysis rate. Higher biomethane noted for sonic wave coupled Iturin A with alkaline pH method. Sonic wave coupled Iturin A with alkaline pH method attained energy ratio of 1.51. Abstract: In this study, sonic wave coupled Iturin A with alkaline pH mediated pre-disintegration was executed to attain enhanced biocellular substance release and upsurge the amenability of water hyacinth biomass (WHBI) towards bio-methanation. During pre-disintegration of WHBI sample, sonic wave coupled Iturin A with alkaline pH 11 necessitated less specific energy of 12110 kJ/kg TS for attaining 30 % of biomass lysis rate when compared to sonic wave coupled Iturin A method (specific energy: 21192 kJ/kg TS, biomass lysis rate: 22.7 %) and sole sonic wave method (specific energy: 35321 kJ/kg TS, biomass lysis rate:15.7 %). Then, pre-disintegrated WHBI samples were subjected to bio-methanation in which sonic wave coupled Iturin A with alkaline pH method attained higher biomethane production value (69 L/kg COD) than sonic wave coupled Iturin A method (52 L/kg COD), sonic wave method (41 L/kg COD), Iturin A method (35 L/kg COD) and control (11 L/kg COD). Further, the cost evaluation of pre-disintegration methods was proceeded in which sonic wave coupled Iturin A with alkaline pH method achieved net profit of 13.4 per ton of WHBI sample.